Pengembangan Buku Pop-Up Berbasis Kearifan Lokal di Demak untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar - Susanti, Putri Anisa; Bektiningsih, Kurniana (Jurnal Gentala Pendidikan Dasar, 2026)
This study aims to develop, test the feasibility, and measure the effectiveness of pop-up book learning media based on local wisdom in Demak in improving students' cognitive learning outcomes. Using a systematic ADDIE development model, this study was conducted at SDN Trengguli 1, Demak Regency, in the even semester of the 2025/2026 academic year. The research design applied was a quasi-experiment using a one-group pretest-posttest design with 24 students as research subjects. The findings confirmed that pop-up books are very feasible to use, based on a media validation score of 88.89% and material validation of 96.05%. The level of practicality of the media was recorded as very high, reaching 100% based on the educators' responses and 92.30% from the students' responses. The effectiveness analysis showed a statistically significant increase in learning outcomes, marked by a significance value of 0.000 in the paired t-test (p < 0.05). In addition, the N-gain analysis results reached a score of 0.6145 in the small-scale test and 0.6419 in the large-scale test, both of which fall into the moderate category. In conclusion, the development of this media has passed the feasibility test and proven to be effective in improving the cognitive competence of fourth-grade elementary school students.